\(\left\{\left[27\times11-\left(x+12\right)\times8\right]\times3-79\right\}\div5=100\)
\(\left[27\times11-\left(x+12\right)\times8\right]\times3-79=100\times5\)
\(\left[27\times11-\left(x+12\right)\times8\right]\times3-79=500\)
\(\left[27\times11-\left(x+12\right)\times8\right]\times3=500+79\)
\(\left[27\times11-\left(x+12\right)\times8\right]\times3=579\)
\(27\times11-\left(x+12\right)\times8=579:3\)
\(27\times11-\left(x+12\right)\times8=193\)
\(297-\left(x+12\right)\times8=193\)
\(\left(x+12\right)\times8=297-193\)
\(\left(x+12\right)\times8=104\)
\(x+12=104:8\)
\(x+12=13\)
\(x=13-12\)
\(x=1\)
\(k\)\(dung\)\(cho\)\(minh\)\(nhe!\)
{ [ 27 * 11 - ( X + 12 ) * 8 ] * 3 - 79 } : 5 = 100
{ [ 27 * 11 - A * 8 ] * 3 - 79 } : 5 = 100
[ 27 * 11 - A * 8 ] * 3 - 79 = 500
[ 27 * 11 - A * 8 ] * 3 = 579
27 * 11 - A * 8 = 193
( 27 * 11 ) - 193 = 297 - 193 = 104
A * 8 = 104
104 : 8 = 13
X + 12 = 13
13 - 12 = 1
vậy X là 1